Lei 13.465/17 e gestão coletiva da terra: o desafio da regularização fundiária em territórios quilombolas urbanos - Nayara Felix Moura Macedo (2024)
This work focuses on investigating the relationship between Law 13,465/17 and the potential for land regularization alternatives that respect and promote collective land management, through a case study at Quilombo Manzo, located in Belo Horizonte. This study aims to understand how the Manzo community has resisted and adapted existing norms to maintain control of its territory, protecting its cultural practices, traditions and way of living, which is based on collectivity and the appreciation of land as a common good. and sacred.